Contemporary debates in epistemology - Steup, Matthias; Sosa, Ernest (Malden, MA : Blackwell Pub., 2005)
"Eleven pairs of newly commissioned essays face off on opposite sides of fundamental problems in current theories of knowledge. This distinctive format offers readers a unique opportunity to observe philosophers engaging in head-to-head debate. The essays are centered on three core areas of epistemology: skepticism, the foundations of knowledge, and justification."--Jacket
I: Knowledge and skepticism / Matthias Steup -- 1. Is knowledge closed under known entailment? -- The case against closure / Fred Dretske -- The case for closure / John Hawthorne -- Reply to Hawthorne -- 2. Is knowledge contextual? -- Contextualism contested / Earl Conee -- Contextualism defended / Stewart Cohen -- Contextualism contested some more -- Contextualism defended some more -- 3. Can skepticism be refuted? -- The refutation of skepticism / Jonathan Vogel -- The challenge of refuting skepticism / Richard Fumerton -- 4. Is there a Priori knowledge? -- In defense of the a Priori / Laurence BonJour -- There is no a Priori / Michael Devitt -- Reply to Devitt -- Reply to BonJour -- Last rejoinder -- II: Foundational knowledge / Matthias Steup -- 5. Is infinitism the solution to the regress problem? -- Infinitism is the solution to the regress problem / Peter Klein -- Infinitism is not the solution to the regress problem / Carl Ginet -- Reply to Ginet -- Reply to Klein -- 6. Can beliefs be justified through coherence alone? -- Non-foundationalist epistemology: holism, coherence, and tenability / Catherine Z. Elgin -- Why coherence is not enough: a defense of moderate foundationalism / James van Cleve -- 7. Is there immediate justification? -- There is no immediate justification / James Pryor -- Doing without immediate justification / Michael Williams -- 8. Does perceptual experience have conceptual content? -- Perceptual experience has conceptual content / Bill Brewer -- Perception and conceptual content / Alex Byrne -- III: Justification / Matthias Steup -- 9. Is justification internal? -- Justification is not internal / John Greco -- Justification is internal / Richard Feldman -- 10. Is truth the primary epistemic goal? -- Truth is not the primary epistemic goal / Johnathan Kvanvig -- Truth as the primary epistemic goal: a working hypothesis / Marian David -- 11. Is Justified belief responsible belief? -- Justified belief as responsible belief / Richard Foley -- Obligation, entitlement, and rationality / Nicholas Wolterstorff -- Response to Wolterstorff -- Response to Foley
Includes bibliographical references and index
Keywords: Knowledge, Theory of